2012
DOI: 10.2307/41703508
|View full text |Cite
|
Sign up to set email alerts
|

MetaFraud: A Meta-Learning Framework for Detecting Financial Fraud

Abstract: Financial fraud can have serious ramifications for the long-term sustainability of an organization, as well as adverse effects on its employees and investors, and on the economy as a whole. Several of the largest bankruptcies in U.S. history involved firms that engaged in major fraud. Accordingly, there has been considerable emphasis on the development of automated approaches for detecting financial fraud. However, most methods have yielded performance results that are less than ideal. In consequence, financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(97 citation statements)
references
References 72 publications
3
94
0
Order By: Relevance
“…Chen et al (2012) highlight five big data applications for business intelligence based on the new generation of data analytics savvy. Hu et al (2012) use network analytics for risk management and Abbasi et al (2012) employ a meta-learning framework for detecting financial fraud. Klassen and Vereecke (2012) discuss social issues in supply chain and Wuttke et al (2013) summarize some typical methods of financial supply chain management.…”
Section: Evolution Of Financial Datamentioning
confidence: 99%
“…Chen et al (2012) highlight five big data applications for business intelligence based on the new generation of data analytics savvy. Hu et al (2012) use network analytics for risk management and Abbasi et al (2012) employ a meta-learning framework for detecting financial fraud. Klassen and Vereecke (2012) discuss social issues in supply chain and Wuttke et al (2013) summarize some typical methods of financial supply chain management.…”
Section: Evolution Of Financial Datamentioning
confidence: 99%
“…Methods for fraud detection have been widely studied. One research stream has designed detection mechanisms to analyze and cope with various fraud types, such as financial fraud (Abbasi, Albrecht, Vance, & Hansen, 2012) and management fraud (Cecchini, Aytug, Koehler, & Pathak, 2010). The methods proposed in this line of research usually require designing a model with a set of cues specific to that particular fraud.…”
Section: Fraudulent Rater Detectionmentioning
confidence: 99%
“…Several studies have reported that BI systems facilitate organisational decision-making by identifying opportunities and problems (Truxillo et al, 2012) and by detecting trends or patterns in customer behaviours (Chau & Xu, 2012), operations (VanDiver et al, 2009 and business processes (Elbashir & Williams, 2007). In a recent special issue on BI in MIS Quarterly, many of the articles see BI systems as a technology that focuses on extracting intelligence or new insights from implementing BI methods and techniques (Abbasi et al, 2012;Hu et al, 2012;Lau et al, 2012;Park et al, 2012;Sahoo et al, 2012). The process of extracting insights and using these to drive action is directly linked to processes of organisational knowing (Choo, 1998).…”
Section: U N Pac K I N G P E R S P E C T I V E S O N B I a N D O R G mentioning
confidence: 99%